2021
DOI: 10.1016/j.transci.2020.102955
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma therapy in patients with COVID-19

Abstract: Passive antibody therapy has been used to immunize vulnerable people against infectious agents. In this study, we aim to investigate the efficacy of convalescent plasma (CP) in the treatment of severe and critically ill patients diagnosed with COVID-19. Method: The data of severe or critically ill COVID-19 patients who received anti-SARS-CoV-2 antibody-containing CP along with the antiviral treatment (n = 888) and an age-gender, comorbidity, and other COVID-19 treatments matched severe or critically ill COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 20 publications
(17 reference statements)
2
52
0
1
Order By: Relevance
“…Our results were also comparable with a recent publication of Altuntas et.al, in which they have concluded that, CP therapy seems to be effective for a better course of COVID-19 in severe and critically ill patients in a Turkish patient cohort [11].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were also comparable with a recent publication of Altuntas et.al, in which they have concluded that, CP therapy seems to be effective for a better course of COVID-19 in severe and critically ill patients in a Turkish patient cohort [11].…”
Section: Discussionsupporting
confidence: 92%
“…We congratulate the authors for conducting a retrospective cohort study of all severe and critically ill COVID-19 patients based on electronic records of the Turkish Ministry of Health. The study included all 888 patients with the exposure (CP transfusion) and a subsample of those unexposed (n = 888), matched to cases on potential confounders including age, gender, comorbidity, and the antiviral treatments used [4]. Having a comparable control group was the main asset of the study design, however, information was missing on: 1) the total number of severe and critically ill patients (target population); 2) total number of eligibles with matched characteristics and whether a representative sampling strategy was used for reaching the final "unexposed" group.…”
Section: Convalescent Plasma (Cp) Therapy In Patients With Covid-19mentioning
confidence: 99%
“…Anti-SARS-CoV-2 antibody-containing CP was found to be significantly and negatively associated with the length of intensive care unit stay, need for mechanic ventilation and need for vasopressor state, yet the case-fatality rate (CFR) was not significantly lower (24.7 % vs. 27.7 %). We wonder whether the non-significant effect of CP on CFR could be explained, at least partially, by "confounding by indication" [6], as a result of prescribing CP to patients based on physicians' expectation of a worse outcome in these patients due to factors other than those matched on (Table 1) [4], such as levels of infection-related biomarkers or inflammatory cytokines. It is also of concern, whether the use of steroids and/or anticoagulants was similar in patients across the groups.…”
Section: Convalescent Plasma (Cp) Therapy In Patients With Covid-19mentioning
confidence: 99%
See 2 more Smart Citations